2016
DOI: 10.1182/blood.v128.22.4565.4565
|View full text |Cite
|
Sign up to set email alerts
|

Effective Treatment of Severe Chronic Graft Versus Host Disease with a Combination of B-Cell Depletion and Tyrosine Kinase Inhibition

Abstract: Introduction Chronic Graft Versus Host Disease (cGVHD) has a large impact on morbidity and mortality after allogeneic hematopoietic stem cell transplantation (HSCT). Therapeutic approaches for cGVHD are limited. Affected patients require long-term use of immunosuppressive drugs, mainly corticosteroids combined with a calcineurin inhibitor, which lead to severe side effects. Options for second line therapy are numerous but no consensus on the most favourable choice of agents has been reached. Bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Van der Wagen et al reported two cases (one viral encephalitis and one Guillain-Barre syndrome) related to the use of rituximab followed by nilotinib as treatment strategy for sclerotic GVHD. 32 Regarding the rest ten prospective studies, immune-mediated and PNS complications as neuromuscular manifestations of GVHD were examined by Koeppen et al 33 Beglinger 34 and Scherwath 35 investigated a different type of neurotoxicity of allo-HCT, that is, cognitive impairment and higher cortical functions. Sostak et al 36 prospectively evaluated a variety of neurologic complications (infectious, cerebrovascular, metabolic, and PNS) after allo-HCT.…”
Section: Descriptive Characteristics Of Each Study Categorymentioning
confidence: 99%
“…Van der Wagen et al reported two cases (one viral encephalitis and one Guillain-Barre syndrome) related to the use of rituximab followed by nilotinib as treatment strategy for sclerotic GVHD. 32 Regarding the rest ten prospective studies, immune-mediated and PNS complications as neuromuscular manifestations of GVHD were examined by Koeppen et al 33 Beglinger 34 and Scherwath 35 investigated a different type of neurotoxicity of allo-HCT, that is, cognitive impairment and higher cortical functions. Sostak et al 36 prospectively evaluated a variety of neurologic complications (infectious, cerebrovascular, metabolic, and PNS) after allo-HCT.…”
Section: Descriptive Characteristics Of Each Study Categorymentioning
confidence: 99%